2022
DOI: 10.3390/fishes8010012
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Stocks of the Redtail Scad Decapterus kurroides Bleeker, 1855 (Perciformes: Carangidae) from the Northern Sulu and Southern Sibuyan Seas, Philippines Revealed from Otolith Morphometry and Shape Analysis

Abstract: A recent study was performed to assess the morphometric variation of otoliths of the Decapterus kurroides collected in the northern Sulu and southern Sibuyan seas in delineating fish stocks. Seven of the otolith morphometric descriptors (otolith length, OL; otolith height, OH; otolith weight OW; otolith area, OA; otolith perimeter, OP; ellipticity, EL; and aspect ratio, AR) demonstrated a significant positive correlation with fish length and six (rectangularity, RE; squareness, SQ; roundness, RO; circularity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…The length range of the redtail scad was 14.7-45.0 cm TL. The largest scad from this study is larger than those from the Lingayen Gulf (25.5 cm) [15], Visayan Sea (28.5 cm), Davao Gulf (24.5 cm) [16], Samar Sea (29.5 cm) [17], Sulu (15.8 cm to 25.7 cm), Sibuyan Sea (16.2 cm to 21.3 cm), [18], and Iligan Bay, Southern Philippines (9.20 cm to 44.50 cmTL) [19]. This size gap may be caused by differences in ecological factors and spatial shifts in fishing pressure [20].…”
Section: Resultsmentioning
confidence: 99%
“…The length range of the redtail scad was 14.7-45.0 cm TL. The largest scad from this study is larger than those from the Lingayen Gulf (25.5 cm) [15], Visayan Sea (28.5 cm), Davao Gulf (24.5 cm) [16], Samar Sea (29.5 cm) [17], Sulu (15.8 cm to 25.7 cm), Sibuyan Sea (16.2 cm to 21.3 cm), [18], and Iligan Bay, Southern Philippines (9.20 cm to 44.50 cmTL) [19]. This size gap may be caused by differences in ecological factors and spatial shifts in fishing pressure [20].…”
Section: Resultsmentioning
confidence: 99%
“…Munoz-Lechuga found some differences in the otoliths of Euthynnus in the Eastern Atlantic and the Mediterranean Sea, based on R language analyses of otoliths [43]. What is more, it has been shown that Decapterus kurroides is not the same stock from the Northern Sulu and Southern Sibuyan Seas [44], based on R language analyses of otoliths. All of the above studies have shown that otoliths (R language method) work well for stock discrimination, and that the same population in the same waters may consist of more than one stock.…”
Section: Discussionmentioning
confidence: 98%